Propuesta de turismo rural comunitario en Palmor de la Sierra Nevada de Santa Marta, Corregimiento de Ciénaga Magdalena - Valencia Ariza, Cáceres Villareal Paula Andrea Angee Virginia (Universidad Antonio Nariño, 2022)
Palmor beyond being a magical town due to the quality of its people and its excellent climate, it has the possibility of providing unique experiences for each person. The proposal for rural community tourism in Palmor de la Sierra Nevada de Santa Marta, Magdalena swamp district, arises from the need to give a new approach to the destination of Palmor, with a sustainable and profitable way for the local community, generating a new vision and allowing a development both in its tourism and its infrastructure. Through this proposal it is sought to respond to the current problems in the territory, generating in turn a new perspective and thus establishing that tourism, beyond knowing an attractive place, is the appropriation of it while respecting the identity of the place. Throughout this work, the different consequences of an excessive and uncontrolled tourism that has been generated over the years in Palmor are explained, comparing it with the similar situation in other places, as well as exposing a new strategy where all the parties involved can have a favorable response, which allows the care and development of the place as the main objective.